IMPROVING THE QUALITY OF EDUCATION SERVICES THROUGH QUALITY MANAGEMENT SYSTEM ISO 9001: 2008 - A Rohim TARMIZI (Journal of Education and Leadership in Education, 2019)
The purpose of this study was to evaluate the implementation of Quality Management System ISO 9001:2008 at SMK (Vocational Senior Secondary School) Putra Bangsa Depok. The researcher used qualitative evaluation method CIPP to examine the agreement between the implementation of Quality Management System ISO 9001:2008 and the principle of ISO. The study concluded: (1) Overall, the implementation of Quality Management System ISO 9001:2008 at SMK Putra Bangsa Depok already ran well, (2) The facilities are clean and comfortable, the human resources as the organizer of management was proactive enough to increase the educational service quality. This could be seen from condusive organizational culture, the work ethos and organizational discipline were good as well as the discipline of the teachers and administrators, (3) The strength of SMK Putra Bangsa Depok was its ability to integrate or combine the curriculum with culture to accomplish customer satisfaction. This research recommends: (1) The headmaster of SMK Putra Bangsa Depok endorses the reform of school committee more actively to play role in cunstructing school programs, (2) the headmaster of SMK Putra Bangsa Depok should be proactive to help all teachers with sufficient qualification get professional certificate